A Review of Phosphorus Removal Structures: How to Assess and Compare Their Performance - Penn, Chad; Chagas, Isis; Klimeski, Aleksandar; Lyngsie, Gry (MDPI, 2017)
Controlling dissolved phosphorus (P) losses to surface waters is challenging as most conservation practices are only effective at preventing particulate P losses. As a result, P removal structures were developed to filter dissolved P from drainage water before reaching a water body. While many P removal structures with different P sorption materials (PSMs) have been constructed over the past two decades, there remains a need to evaluate their performances and compare on a normalized basis. The purpose of this review was to compile performance data of pilot and field-scale P removal structures and present techniques for normalization and comparison. Over 40 studies were normalized by expressing cumulative P removal as a function of cumulative P loading to the contained PSM. Results were further analyzed as a function of retention time (RT), inflow P concentration, and type of PSM. Structures treating wastewater were generally more efficient than non-point drainage water due to higher RT and inflow P concentrations. For Ca-rich PSMs, including slag, increased RT allowed for greater P removal. Among structures with low RT and inflow P concentrations common to non-point drainage, Fe-based materials had an overall higher cumulative removal efficiency compared to non-slag and slag materials.
Keywords: phosphorus removal; phosphorus sorption materials; best management practices; legacy phosphorus; urban stormwater; fosfori; vedenlaatu; hulevesi; phosphorus; water quality; storm water; water management